Diagnóstico parasitológico en camélidos sudamericanos en la comunidad de Apagua. - Tutasig Coque, Mauricio Bladimir (2021)
This research project was conducted in the community of Apagua, Cotopaxi province, with the objective of diagnosing the presence of external and internal parasites of South American camelids using the field methodology for the laboratory analysis of the population of the parasite genus with the flotation technique and for the external parasites the technique of the KOH test at 10¸ for which we used as an instrument surveys to institutions participating in the technical assistance and to directors of the association alpaquera Tarpuy observing the prevalence of Haemonchus spp and Nematodirus spp 42. 8%, adding Chabertia appears with 28. In relation to the schedule of deworming, it was concluded that ivermectin is used most frequently, followed by Albendazole and in third place Febendazole, and it was analyzed that the presence of other animals in the environment, such as llamas, sheep and cattle, constitute vectors of the parasites, The presence of other animals in the environment such as llamas, sheep and cattle are vectors of parasitic diseases such as Chabertia, recommending that in order to plan a deworming calendar it is necessary to orient ourselves with the results of the parasitic population and a table of specificity of pharmaceutical products to be used.